Spectral Analysis of Surface Waves (SASW) Measurement For Soil Characterization - Gunawan Handayani (Institut Teknologi Bandung, 2006)
In geotechnical engineering and earthquake engineering, the information of seismic shear wave velocity profile of the subsurface is vital in assessing the strength of soil layers, estimating the ground shaking during earthquake and liquefaction potential of the soil layers. Conventional method in determining the shear wave velocity profile is conducting seismic down hole or cross hole which requires drilling some boreholes. Recent popular method is to carry out surface wave survey that does not require any boreholes. This paper reports the results of one of surface wave method i.e. the Spectral Analysis of Surface Wave (SASW) for soil characterization in Banda Aceh. The field procedure and data processing including the phase unwrapping process which is very important to obtain an accurate field dispersion curve are discussed. The results of the survey in terms of shear wave profile are used in predicting the ground shaking during earthquake.